2008
DOI: 10.1016/j.freeradbiomed.2007.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Roles of nitric oxide in inflammatory downregulation of human cytochromes P450

Abstract: The purpose of this study was to determine the role of nitric oxide (NO) in the down-regulation of human CYP enzymes and mRNAs by an inflammatory stimulus in cultured human hepatocytes. We focused on CYP2B6, because previous studies showed that rat CYP2B proteins undergo an NOdependent degradation in response to inflammatory stimuli. To ensure high level expression of CYP2B6, the inducer phenytoin was present at all times. Stimulation of cells with a mixture of TNFα, IL-1β and IFNγ (ILmix) down-regulated CYP2B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 44 publications
3
43
0
3
Order By: Relevance
“…CYP3A4 mRNA is down-regulated by proinflammatory cytokine treatments in primary human hepatocytes (Aitken and Morgan, 2007;Aitken et al, 2008), but neither its mRNA nor protein down-regulation is NO-dependent. The NO-responsiveness of human CYP3A5 and CYP3A7 remains to be determined.…”
mentioning
confidence: 94%
“…CYP3A4 mRNA is down-regulated by proinflammatory cytokine treatments in primary human hepatocytes (Aitken and Morgan, 2007;Aitken et al, 2008), but neither its mRNA nor protein down-regulation is NO-dependent. The NO-responsiveness of human CYP3A5 and CYP3A7 remains to be determined.…”
mentioning
confidence: 94%
“…The role of higher NO levels in causing a feedback loop triggering anti-inflammatory mechanisms can be a potential therapeutic approach in NASH, given the use of an NO donor in a single study for NASH remediation involving ob/ob mice, the spontaneous knockout (KO) of leptin, where no mechanistic inputs were provided (de Oliveira et al, 2008). Along with studies of the boosting of NO levels are the extensive studies about the role of NO in inhibiting CYP2E1; the use of an NO donor to treat NASH can be an excellent regimen (Gergel et al, 1997;Aitken et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We showed previously that, similar to rat CYP2B1, human CYP2B6 protein undergoes NO-dependent downregulation in human hepatocytes (Aitken et al, 2008). In addition to CYP2C22, Qian et al (2010) showed the related human CYP2C9 mRNA to be regulated by atRA.…”
Section: Discussionmentioning
confidence: 78%
“…We have shown that NO produced by interleukin-1 (IL-1)b or lipopolysaccharide stimulation of hepatocytes causes ubiquitin-dependent proteasomal degradation of the rat phenobarbital-inducible P450 CYP2B1 (Ferrari et al, 2001;Lee et al, 2008;Sun et al, 2012). The related human enzyme CYP2B6 also undergoes downregulation at the protein level in response to NO (Aitken et al, 2008).…”
Section: Introductionmentioning
confidence: 99%